Re-Evaluation of Imaging Methods of Reactive Oxygen and Nitrogen Species in Plants and Fungi: Influence of Cell Wall Composition - Sedlářová, Michaela; Luhová, Lenka (Frontiers in Physiology, 2017)
Developmental transitions and stress reactions in both eukaryotes and prokaryotes are tightly linked with fast and localized modifications in concentrations of reactive oxygen and nitrogen species (ROS and RNS). Fluorescent microscopic analyses are widely applied to detect localized production of ROS and RNS in vivo. In this mini-review we discuss the biological characteristics of studied material (cell wall, extracellular matrix, and tissue complexity) and its handling (concentration of probes, effect of pressure and higher temperature) which influence results of histochemical staining with “classical” fluorochromes. Future perspectives of ROS and RNS imaging with newly designed probes are briefly outlined.